Impact of Entrepreneurship Activity Sustainable Development - Huđek, Ivona; Hojnik, Barbara Bradač (Problemy Ekorozwoju, 2020)
Sustainable development considers the development that achieves the present economic goals, without obstructing the future development in a sense of satisfying the needs of society and endangering the environment. Recently, the entrepreneurship phenomenon has been widely recognized as an important path towards sustainable development, positively contributing to the development of society. Thus, in the paper, the empirical evidence on linkages between entrepreneurial activity indicators and social development goals is provided. To examine the linkages, the data from the Global Entrepreneurship Monitor and Sustainable Development Goals Index were used. The empirical results suggest that entrepreneurship represents an important factor for fostering sustainability, particularly in opportunity-driven and innovative entrepreneurial activities. The results show, that both of them have a positive impact on sustainable development, while the necessity-driven entrepreneurial activity negatively affects sustainable development. This could be explained by the fact that necessity entrepreneurs are not likely to become the entrepreneurs to implement a promising business opportunity, but rather to earn an income. To achieve the sustainable development goals as well as entrepreneurship should become the national priority by introducing new policies and measures, that is, making the conditions, through which entrepreneurship could achieve positive contributions to the development of the society.